O cânone em movimento : um estudo da leitura de textos canônicos adaptados em livro didático do ensino fundamental - Arraes, Beatriz Pinheiro (2007)
This case study aims at examining how the literature classics are worked in a Fundamental Education school, discussing the concept of canonical literature and the means of circulation of this kind of reading. The educational material of a private school in Presidente Prudente, São Paulo, was analysed, especially concerning the Portuguese material of the fourth grade of the Fundamental Education, verifying the approach used with the canonical texts as well as the proposed activities. The re-reading of these works is analysed, considering new possibilities of reading. Regarding the translation of the texts, there has always been discussions concerning the proximity between the original text and the translated one, between what was said in native language and what was said in another one. This way, the translations and adaptations of the canonical texts were always seen as new meanings, as a dynamic and complex process that updates a permanent discourse. In this way, the kinds of practices offered to the students were verified as well as how they collaborate to the formation of different discourses that materialize in the day-by-day, in the language, in the culture and in the place. Having in mind that mediation is essential for the development of this process of reading, the relation between teacher and text was observed. From the analysis of the summary notebook of the students, it was possible to observe the classroom approach and how much it promoted the meaning construction by the students. Thus, the present work was able to verify how the construction of knowledge concerning the canonical literary productions takes place as well as its importance for the formation of the whole individual.